KURTOSIS - Seier Zúñiga, María Edith (2003)
This work reviews the literature on kurtosis from Pearson'e definition in the early 1900's to our days. The evolution of the concept of kurtosis is described and the different ways of quantifying it are compared; graphs that help to understand the ideas are included. Kurtosis is also discussed in the context of bimodality and tests for normality. Simulation results and comments based on our work on the topic are included.